SOSIOLOGI SEBAGAI PENDEKATAN PEMAHAMAN AGAMA DAN KITAB SUCI - Sholihah, Izzatus (SAMAWAT: Journal Of Hadith and Qur'anic Studies, 2021)
Generally, sociology can be understood as the study of human social life in the order of life together. This science focuses on the study of group life and social behavior complete with the products of life. With this science, a social phenomenon can be analyzed by the factors that encourage relationships, social mobility and the beliefs that underlie the process.Furthermore, sociology can be used as an approach in understanding religion. This is because many new fields of religious studies can be understood proportionally and appropriately when using assistance from sociology. Moreover, today the presence of religion is increasingly required to be actively involved in solving various problems faced by mankind. Religion should not just become a symbol of piety or stop just being preached in a sermon, but conceptually show the most effective ways of solving problems.